Bone Gap - Ruby, Laura (New York, NY : Balzer + Bray, an imprint of HarperCollinsPublishers, 2015)
Eighteen-year-old Finn, an outsider in his quiet Midwestern town, is the only witness to the abduction of town favorite Roza, but his inability to distinguish between faces makes it difficult for him to help with the investigation, and subjects him to even more ridicule and bullying.
The people of Bone Gap -- Roadkill -- Run -- Showdown -- Jump -- The night mare -- The promise ring -- Storming the castle -- Sees the fire -- Just like the rest of us -- Lost -- Good for you -- Get real -- No one is fine -- Sidetracked -- The whole picture -- Questions -- The lamb -- Blindside -- The dead -- Punched -- The ballad of Charlie Valentine -- The fields -- Crows -- Slaughter -- Sunrise -- The people of Bone Gap.
Accelerated Reader
Keywords: Michael L. Printz Award, 2016; Kidnapping -- Juvenile fiction; Face perception -- Juvenile fiction; Teenage immigrants -- Crimes against -- Juvenile fiction; Feminine beauty (Aesthetics) -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Bullying -- Juvenile fiction; Brothers -- Juvenile fiction; Kidnapping -- Fiction; Face perception -- Fiction; Interpersonal relations -- Fiction; Bullying -- Fiction; Brothers -- Fiction; Young adult fiction; Magical realism (Literature); Michael L. Printz book award: Winner -- 2016.